2022
DOI: 10.3389/fneur.2022.891368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiovascular Concerns of Intravenous Lacosamide Therapy in Epilepsy Patients

Abstract: ObjectiveVoltage-gated sodium channels (VGSCs) play an important role in neuronal excitability and epilepsies. In addition to the brain, VGSCs are also abundant enriched in cardiac tissues and are responsible for normal cardiac rhythm. Theoretically, sodium channel blocking antiseizure medications (SCB-ASMs) may have unwanted cardiac side effects. Lacosamide (LCM) is increasingly used in patients with status epilepticus (SE) due to the availability of intravenous formula. The concerns about the proarrhythmic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
(42 reference statements)
1
5
1
Order By: Relevance
“…Kim et al reviewed medical records of consecutive adult epilepsy patients who received a single loading dose (400 mg) of IV LCM, 32.9% (28/85 patients) had experienced at least one cardiac AE 11 . Our mining data showed that cardiac adverse reactions had a higher proportion of serious outcomes (91% vs 74.29%) and a higher risk of life-threatening (14.48% vs 3.48%) than other adverse reactions, which is inconsistent with other studies 8 , 10 , 20 . Additionally, the median age of 49 years indicates that cardiac AEs can occur across a wide range of ages, emphasizing the need for vigilance regardless of the patient's age.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Kim et al reviewed medical records of consecutive adult epilepsy patients who received a single loading dose (400 mg) of IV LCM, 32.9% (28/85 patients) had experienced at least one cardiac AE 11 . Our mining data showed that cardiac adverse reactions had a higher proportion of serious outcomes (91% vs 74.29%) and a higher risk of life-threatening (14.48% vs 3.48%) than other adverse reactions, which is inconsistent with other studies 8 , 10 , 20 . Additionally, the median age of 49 years indicates that cardiac AEs can occur across a wide range of ages, emphasizing the need for vigilance regardless of the patient's age.…”
Section: Discussioncontrasting
confidence: 99%
“…Experimental studies and clinical trials indicate that LCM affects neuronal and cardiac activity, potentially raising the likelihood of cardiac arrhythmias 19 . Like other anticonvulsant drugs, the dose-dependent inhibition of sodium channels by LCM may lead to delays in cardiac conduction below the level of the His bundle, potentially contributing to the development of cardiac arrhythmias 8 , 11 . The available studies on cardiac AEs associated with LCM use have limitations in sample size and lack of data stratification by sex, age, and weight, highlighting the importance of ongoing post-marketing surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both epilepsy and ASMs were found to be associated with an elevated risk of cardiovascular diseases. ASMs prolong the QT interval by closing ion channels or delaying their opening, thereby affecting cardiac rhythm and increasing the risk of arrhythmias in susceptible individuals, which provides a pathophysiological basis for ASM-induced arrhythmias ( 10–12 ).…”
Section: Introductionmentioning
confidence: 99%